Combination Treatment With Metformin and Tacrolimus Improves Systemic Immune Cellular Homeostasis by Modulating Treg and Th17 Imbalance - Lee, Soon Kyu; Park, Min-Jung; Jhun, Joo Yeon; Beak, Jin-Ah; Choi, Jeong Won; Rye, Jae-Yoon; Jang, Jeong Won; Bae, Si Hyun; Yoon, Seung Kew; Choi, Ho Joong; You, Young Kyoung; Cho, Mi-La; et al. (Frontiers in Immunology, 2021)
We examined the effect of combination therapy with metformin and tacrolimus on immune parameters including T regulatory (Treg) and type 17 helper T (Th17) cells in vitro and in vivo in mice and in liver transplantation (LT) patients. T cell proliferation and subtypes after in vitro T cell activation or allogeneic stimulation were evaluated. RNA sequencing and microarray analysis were used to evaluate differences in gene expression. Metformin and tacrolimus were administered to mice with graft-versus-host disease (GVHD) and the effects in vivo were assessed. Five LT patients were treated with metformin and the changes in Treg and Th17 cells examined. Combination therapy decreased Type 1 helper T (Th1) and Th17 cells present after in vitro T cell activation, whereas genes associated with Treg were overexpressed. During in vitro allogeneic stimulation, combination therapy increased Treg cells and decreased T cell proliferation and pro-inflammatory markers. In mice with GVHD, combination treatment decreased the clinical and pathological severity of GVHD. In LT patients, addition of metformin increased the peripheral percentage of CD4+Treg and CD8+Treg cells and decreased CD4+Th17. Our study suggests that the addition of metformin to tacrolimus may improve immunological balance by increasing Treg cells and decreasing Th17 cells.